Noninvasive cardiac output measurement based optimization in nonresponders of cardiac resynchronization therapy. Issue 4 (7th April 2020) - Yenerçağ, Mustafa; Yüksel, Serkan; Çoksevim, Metin; Akçay, Murat; Arslan, Uğur
Abstract: Background: Cardiac resynchronization therapy (CRT) is an important and effective therapy for end‐stage heart failure (HF). Nonresponse to CRT is one of the main obstacles to its application in clinical practice. Herein, we investigated the utilization of the optimization technique using noninvasive cardiac output measurement (NICOM) based Mobil‐O‐Graph device that measures several circulation parameters noninvasively. Methods: Seventy‐five CRT nonresponder HF patients with an implanted CRT device were included. Patients were randomized equally to 3 groups: NICOM, echocardiographic, and empirical optimization groups. After 3 months of optimization, changes in six minutes walk test (6‐MWT), cardiac output (CO), left ventricular ejection fraction (LVEF), and end‐systolic volume (LVESV) were measured. New York Heart Association (NYHA) class and hospitalization for HF were also determined. Results: There were no statistically significant differences among the three groups in terms of demographics, baseline characteristics. In the NICOM group, the 6‐MWT, LVEF, CO, and LVESV measurements showed significant improvements compared to baseline values ( P  < .05). There was no significant improvement in 6‐MWT, LVEF, CO, NYHA class, and LVESV in Echo and Empirical groups after 3 months ( P  > .05). 6‐MWT, CO, LVESV percentages, and hospitalization for HF were significantly different between the groups ( P  < .05). In post hoc analyzes, the percentages of the change in 6‐MWT, CO, LVESV, and hospitalization for HF were significantly higher in the NICOM group ( P  < .017). Conclusions: This study suggests that Mobil‐O‐Graph device optimization according to CO measures does appear to have potential hemodynamic and clinical benefits in nonresponder CRT patients. Use of Mobil‐O‐Graph device as an option for optimization of CRT devices can be an attractive method of improving CRT outcomes.